2011
DOI: 10.1111/j.1471-0528.2011.03149.x
|View full text |Cite
|
Sign up to set email alerts
|

The origin of ovarian cancer

Abstract: A prerequisite for the success of early detection of a disease is the clear understanding of its natural history. The cellular origin of ovarian cancer has remained elusive, and this has delayed our understanding of the biology of initiation and progression of the disease, and has hampered the development of effective early detection methods. As a consequence, ovarian cancer remains one of the most fatal malignancies in women worldwide. In this issue of BJOG Sharma et al. present important evidence from a pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…Moreover, drug-resistant dormant ovarian cancer cells persist for several months in the peritoneal cavity (1), (2), (3). Other investigators have shown that most metastatic ovarian ascites cancer cells are in a dormant, reversibly quiescent state (4), and such cells can go back into cycle when they implant on the peritoneum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, drug-resistant dormant ovarian cancer cells persist for several months in the peritoneal cavity (1), (2), (3). Other investigators have shown that most metastatic ovarian ascites cancer cells are in a dormant, reversibly quiescent state (4), and such cells can go back into cycle when they implant on the peritoneum.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian cancer often spreads by local shedding into the peritoneal cavity. Drug-resistant dormant ovarian cancer cells can persist for several months in the peritoneal cavity (1), (2), (3). The implantation of exfoliated ovarian cancer cells on the peritoneum leads to ascites formation and local invasion of the bowel and bladder.…”
Section: Introductionmentioning
confidence: 99%
“…33 Because our study was designed to be exploratory, we deliberately included different histologic subtypes of ovarian cancer, because we were acutely aware of the recent controversy regarding their differing origin and pathogenesis. 34,35 Nevertheless, the vast majority of our patients, particularly in the validation cohort, were diagnosed with advanced stage, high-grade, serous ovarian cancer. Hence, we propose the further evaluation of TUSC3 as a prognostic factor primarily in this subset of patients with ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Although TP53 mutations are a hallmark of HGS-OvCa (9, 11, 23), the role that mutant p53 variants play in the acquisition of these phenotypes is currently not known.…”
Section: Introductionmentioning
confidence: 99%